Assisted reproductive technology in Nigeria: tackling the issues of commodification and the dearth of legal regulation (2018)
Having children is an extremely important event in the life of individuals, particularly married couples. The success and advancement attributed to invention of assisted reproductive technology (ART) in developed countries, and developing countries such as Nigeria has now made it possible for infertile persons and couples who would otherwise have been unable to conceive and bear children to now have children. However, despite the feats and advancement of medical science in this area, infertility or inability to conceive remains a problem of global proportions. In many developing countries, particularly sub-Sahara countries like Nigeria, ARTs and other related services remain ill-regulated and expensive, leading to abuse, exploitation and commodification. This article examines the issue of commodification in various means of assisted reproductive technology, the various abuses of commodification such as the ‘baby factories ’ and sale of babies in Nigeria. The article exposes the challenges facing assisted reproduction and ill-regulation in Nigeria. The article advocates for a specific legislation to curb the nefarious practice of ‘commodification ’ and also, the recognition and promotion of the reproductive rights of infertile individuals and couples to access and benefit from ARTs